Hierarchical control architecture for mobile offshore bases - A. Girard (2000)
A hierarchical architecture for Mobile Offshore Bases (MOB) control is presented. By a control architecture we mean a specific way of organizing the motion control and navigation functions performed by the MOB. It is convenient to organize the functions into hierarchical layers. This way, a complex design problem is partitioned into a number of more manageable sub-problems that are addressed in separate layers. The decomposition also allows for modular design and testing and the incorporation of plug-and-play components. This paper discusses the MOB require ments and maps them onto a layered control architecture. The formalization of the hierarchy is accomplished in terms of the specific functions accomplished by each layer and of the interfaces between layers. The implementation of the layers is discussed and illustrative examples are provided.